The Role of Banking Competitiveness in Increasing National Income through the Transmission Mechanism of The Effects of Bank Lending Channel of Monetary Policy - Bahtiar Usman; Dhea Vanesa Emuldo; Syofriza Syofyan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
This study aims to determine the role of banking competition in increasing national income through the transmission mechanism of monetary policy credit channel. The dependent variable in this study is gross domestic product (GDP), while the independent variables is BI rate, credit interest rates, banking competition, and lending. This study uses the Vector Autogressive (VAR)method, but because it does not pass the cointegration test, the Vector Error Correction Model (VECM) method is used instead which is part of the Vector Autogressive (VAR) method. By using banking CR4 (concentration ratio of 4 large banks) as a measure of banking competition, it shows that increasing CR4 will reduce banking competition, and reduce investment credit. Investmentcredit is the dominant variable in influencing the National Income variable.